Experimental investigation of electrolytically treated and silane grafted carbon fiber-reinforced thermoplastic polyurethane composites. (June 2023) - Syed, Nabeel Ahmed; Tariq, Muhammad; Utkarsh, Utkarsh; Behravesh, Amir H; Guo, Q; Pop-Iliev, Remon; Rizvi, Ghaus
In this study, the continuous fiber rowing of 12K carbon was electrolytically oxidized by incorporating three different types of electrolytes: Ammonium bicarbonate, Sulfuric acid, and Sodium hydroxide at various concentrations. Upon chemical treatment, the fibers were grafted with 3-Aminopropyl-triethoxysilane (APTS), a silane coupling agent, to achieve better interlocking and compatibility with the thermoplastic polyurethane (TPU) matrix. Mechanical properties were analyzed by tensile tests, morphological analysis was carried out through Scanning Electron Microscopy, and spectral analysis was studied through X-ray photoelectron spectroscopy (XPS) characterizations. The results show that 10% sulfuric acid treatment plus APTS grafted carbon fiber/TPU composites showed an average tensile load capacity of 2528 N, about 39% higher than raw carbon/TPU. The morphological analysis provided compelling evidence for the increase in mechanical properties of modified fiber composites as the interfacial bonding between the electrolytically modified and silane coated fiber/TPU composites was much better than the raw fiber/TPU composites. Further, XPS results confirm that the atomic percentages of Carbon have been reduced, whereas the percentage of oxygen and nitrogen have increased. These compositional changes indicate that the overall interaction between the fiber and the matrix has been enhanced, accounting for improved compatibility between the two interacting phases.